The impact of the non-linguistic context on the interpretation of the verbal act - Marhoun, assia; ammari, azzeddine (El Omda in Linguistics and Discourse Analysis, 2025)
The contemplator of the topic of “context” in general in ancient and modern linguistic studies notices a diversity of concepts and visions, but if we want to gather them, we realize that it has been addressed by two different sayings that were the main starting point in studying the linguistic system and its secretions in various verbal situations, namely: And they make it one of the pillars and frameworks upon which the linguistic use is based, while the second is that its pioneers see that “context” has no presence in the language, as it is outside its phonetic and written nature that can be measured and observed, especially in the framework of the specialization that has become dictated by linguistics. This is what made the deliberative current explain the process of speech production and link it to the addressee, and the recipient who dismantles the linguistic message to reach the speaker’s destination, and therefore the process of speech production and understanding is closely linked to the position that frames the process of speech production, and the attempt to understand these verbal forms depends on knowing all the circumstances and circumstances that surrounded it. The deliberative trend is among the linguistic trends that have reconsidered the study of "context", especially through the theory of speech acts, and this is what we will discuss in this article.